2006
DOI: 10.1002/hyp.6227
|View full text |Cite
|
Sign up to set email alerts
|

Impact of redox and transport processes in a riparian wetland on stream water quality in the Fichtelgebirge region, southern Germany

Abstract: Abstract:Biologically mediated redox processes in the riparian zone, like denitrification, can have substantially beneficial impacts on stream water quality. The extent of these effects, however, depends greatly on the hydrological boundary conditions. The impact of hydrological processes on a wetland's nitrogen sink capacity was investigated in a forested riparian fen which is drained by a first-order perennial stream. Here, we analysed the frequency distributions and time-series of pH and nitrogen, silica, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…The catchment area covers 4.2 km 2 at an elevation between 695 and 877 m.a.s.l. (Lischeid et al, 2007). The mean annual air temperature is 5°C and the mean annual precipitation is approximately 1150 mm (Huang and Matzner, 2007b).…”
Section: Site Description and Hydrogeological Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The catchment area covers 4.2 km 2 at an elevation between 695 and 877 m.a.s.l. (Lischeid et al, 2007). The mean annual air temperature is 5°C and the mean annual precipitation is approximately 1150 mm (Huang and Matzner, 2007b).…”
Section: Site Description and Hydrogeological Modelmentioning
confidence: 99%
“…The regolith overlying the granitic bedrock is 40 m thick and consists of sand, loam, gravel, and granite boulders (Lischeid et al, 2007). The catchment is drained by a dense network of natural streams and artificial ditches.…”
Section: Site Description and Hydrogeological Modelmentioning
confidence: 99%
“…This may also be caused by a simple dilution effect of wetland pore water with groundwater, though. This could not be ruled out based on the available data, as δ 18 O and δ 2 H of shallow wetland groundwater and deep groundwater were not sufficiently different and also chloride could not be used (not shown), but a major contribution of water originating from wetland areas during storm events was already stated by Lischeid et al (2007). Nevertheless, one could expect a formation of a relatively iron enriched flocculation or precipitation product, as has been observed at the site in form of iron rich colloids (Neubauer et al, 2012, unpublished).…”
Section: Processes At the Wetland-stream Interfacementioning
confidence: 99%
“…Maassen & Balla (2010) found that small-scale heterogeneous patterns of groundwater infiltration and exfiltration had substantial impacts on microbial processes and phosphorus turnover in a small stream in Brandenburg. Lischeid et al (2007) observed a complex interplay between hydrological and biochemical processes in a small wetland area, where deep oxic groundwater and reduced shallow groundwater get mixed. Here, residence time of water in the uppermost soil layers seemed to exert a major impact on quality of the discharging water.…”
Section: Introductionmentioning
confidence: 98%